Lithium-ion battery performance modeling based on the energy discharge level. (18th October 2018) - Porras-Hermoso, Ángel; Pindado, Santiago; Cubas, Javier
Abstract: In the present work, a new model for Li-ion battery performance is proposed. This model is based on the energy discharge level (in relation to full capacity), and was developed after testing carried out on the battery of the UPMSat-2 satellite. These thermal vacuum chamber tests showed extremely high energy efficiencies. The results from the proposed model reproduce the test results (discharging/charging processes) of a 17.2 A · h Li-ion battery.